Trouble at the bridge (How I feel, ,, 2000)
As the Lego city builders hurry to complete a new bridge, they face an unusual problem when a bank robber tries to hide in their giant crane.

The whipping boy (Greenwillow Bks, Greenwillow Books, 1986)
NEWBERY COLLECTION. A bratty prince and his whipping boy have many adventures when they inadvertently trade places after becoming involved with dangerous outlaws. Winner of Newbery Award, 1987.

Rivals (Robyn Hood, 2,, 2019)
When a rival gang comes to town and starts stealing from innocent people, can master thief Robyn Hood find a way to give them a taste of their own medicine?

Metropolis orphanage (Robyn Hood, 1,, 2019)
Master thief Robyn Hood must discover who is taking money from a local orphanage before the kids' fates are put in danger.

Mystery at Chilkoot Pass (Pleasant Co. Publications, 2002)
At the start of the Klondike gold rush of 1897, while traveling through Canada with her father, uncle and friends, a twelve-year-old aspiring author Hetty tries to determine the identity of a thief.

Geronimo Stilton reporter: #15,Clean sweep (Papercutz, 2023)
When the owner of the Daily Rat newspaper thinks Thea Stilton, who has vanished without a trace, is responsible for a recent string of robberies in New Mouse City, Geronimo must employ his "famouse" investigative skills to find Thea - and the truth.

The magic misfits (Magic misfits, I,, 2017)
"Six young magicians and illusionists team up to save their small town from a crooked carnival owner and his goons"--

Homer on the case (Peachtree, 2021)
"Homing pigeon Homer and his parrot friend Lulu learn something is afoul when they witness four-legged criminals stealing valuables from both the animal and human communities. Using the sleuthing techniques he's gathered from his favorite mystery comics, Homer and Lulu track down the bandits, but need human help to stop them for good. Can they find a way to communicate with their human keepers and lead them to the culprits' hideout to stop the thieves?"--Publisher marketing.

Theodore Boone: the accomplice (Theodore Boone, 7,, 2019)
"When his best friend Woody is arrested--an unwitting accomplice to a robbery--Theodore Boone must work to prove his innocence"-- Theodore Boone is back on the case in an all-new adventure! Bestselling author John Grisham delivers a page-turning legal thriller for a new generation of readers. Theo has been worried about his good friend Woody Lambert. Woody is struggling at school and making bad choices. But when Woody is arrested--an unwitting accomplice to armed robbery -- Theo knows he is innocent. Racing the clock while Woody sits in jail, Theo will do everything in his power to help his friend and save Woody from an unforgiving system where justice is not equal for all. Brimming with the intrigue and suspense that made John Grisham a #1 international bestseller and undisputed master of the modern legal thriller, Theodore Boone's trials and triumphs will keep readers hooked until the very last pag

Six of crows (Six of crows duology, 1,, 2015)
"Six dangerous outcasts. One impossible heist. Kaz's crew is the only thing that might stand between the world and destruction--if they don't kill each other first"-- Ketterdam: a bustling hub of international trade where anything can be had for the right price--and no one knows that better than criminal prodigy Kaz Brekker. Kaz is offered a chance at a deadly heist that could make him rich beyond his wildest dreams. But he can't pull it off alone: A convict with a thirst for revenge, a sharpshooter who can't walk away from a wager, a runaway with a privileged past, a spy known as the Wraith, a Heartrender using her magic to survive the slums, and a thief with a gift for unlikely escapes. Six dangerous outcasts. One impossible heist. Kaz's crew is the only thing that might stand between the world and destruction--if they don't kill each other first. -- Provided by publisher.